The effect of BCG vaccine at birth on the development of atopy or allergic disease in young children - (:unkn) unknown (AMER COLL ALLERGY ASTHMA IMMUNOLOGY, 2004)
Background: Exposure to infectious diseases may reduce the development of asthma or allergy. In particular, the role of the BCG vaccine in modulating asthma or allergy has been a source of speculation. Objective: To study newborns from 3 international sites to evaluate the prospective effect of BCG vaccine on allergic diseases or atopic development. Methods: Infants were enrolled from newborn and well-infant clinics in Thailand, Argentina, and Turkey. The standard BCG vaccine for each country was given at birth. Parents who consented to have their infant included in the protocol completed an allergy family questionnaire. Infants underwent a standard purified protein derivative (PPD) test at 9 to 12 months of age, and the reaction size was measured. At the age of 2 years, the children returned to be studied. Allergy skin tests to common allergens appropriate to location and age were performed, and the parents completed the International Study of Allergy and Asthma in Childhood questionnaire. The PPD reaction size was compared with the presence of atopy and allergy questionnaire responses. Results: A total of 1,704 infants were studied. Statistical significance was found between a negative PPD response vs any positive PPD response and the risk of having an allergic history at the age of 2 years in Turkey (relative risk, 2.11; 95% confidence interval, 1.25-3.55; P = .005) and Thailand (relative risk, 2.16; 95% confidence interval, 1.18-3.94; P = .02) but not Argentina (relative risk, 1.09; 95% confidence interval, 0.70-1.68; P = .70). Conclusions: This study further supports the role of infectious agents in modulating asthma and allergy development.
Keywords: BACILLE CALMETTE-GUERIN; TUBERCULIN RESPONSES; WORLDWIDE VARIATIONS; CHILDHOOD ISAAC; AIRWAY HYPERRESPONSIVENESS; MYCOBACTERIAL ANTIGENS; ASTHMA SYMPTOMS; PREVALENCE; INFECTION; ABSENCE